Impact of Candida railenensis during fermentation on the aromatic profile of Vidal blanc icewine - Li, Jing; Hong, Mengnan (Frontiers in Microbiology, 2023)
Mixed culture fermentation with non-Saccharomyces yeasts and Saccharomyces cerevisiae as multi-starters has more advantages than spontaneous fermentation, and the wine products with distinctive and pleasant aromas can fulfill the diverse demands of consumers. This study was carried out to illuminate the effect of sequential inoculation of indigenous Candida railenensis and S. cerevisiae on alcoholic fermentation behavior, chemical and aromatic characteristics of Vidal blanc icewine. During the mixed culture fermentation, C. railenensis was present in the initial and middle stages but was absent after 14 days. The results of basic chemical parameters showed that the glycerol content in themixed culture fermented icewine was higher than that of the pure fermented icewine, but the acetic acid content was opposite. In terms of volatile aroma compounds, C. railenensis in the mixed culture fermentation reduced some metabolites such as lower alcohols, 1-hexanol, 3-methylthiopropanol, and their unpleasant notes; and increased the production of some desired volatile aroma compounds such as benzaldehyde, β-damascenone, 2-furanmethanol, 5-methyl furfural associated with rose, honey, nut and caramel characteristics. Furthermore, C. railenensis also changed the sensory performance of icewine by participating in the fermentation of S. cerevisiae. These findings suggest that C. railenensis with the positive enological properties has the ability to be used in icewine production, which has never been reported before.